A Particular Interpretation of the History of Spain - Juan José Morales Ruiz (Journal of Multidisciplinary Studies in Human Rights and Science, 2024)
Franco's speeches are loaded with anti-liberal rhetorical arguments, peppered with anti-communism, anti-Semitism, and anti-Masonry. Many examples can be given. In them, he presented his particular interpretation of the history of Spain, a rhetorical model on which the revisionist theses would later be based. In this sense, we will study, as inspiring sources of the revisionist positions in the study of contemporary history, some examples that reflect his particular analysis of the history of Spain, which will be based on his oft-repeated theory of the Jewish-masonic-communist conspiracy.